SHAXS PSIXOLOGIK MUNOSABATLARINING MOHIYATI VA O‘ZIGA XOSLIGI - Saidova, F.N. (SCIENCE and SOCIETY, 2024)
The article describes interaction in interpersonal relationships. A person’s perception of each other in the process of communication represents the unique inner spiritual world of society and different people in it. The scientists’ interpretation of problems in interpersonal relations is highlighted.
Keywords: interaction; essence; interpersonal relations; society; perception